Strategic Analysis PT Astra International Tbk (ASII) - Andrew Victorio Soetikno; Liliana Inggrit Wijaya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to determine the analysis strategy of PT Astra Internasional TBK (ASII). The data used in the research is secondary data, which we obtained from resumes from several articles. The research results show that based on the results of the analysis at the matching stage, it can be concluded that Astra is taking an aggressive strategy, because Astra is able to handle and carry out management in its seven business units. Astra can also take advantage of the growth in market share from all sectors to increase the Company's competitiveness and become a market leader. So Astra itself chose an aggressive strategy. This is in accordance with SWOT, IE, Grand Strategy, BCG, and SPACE.